(untitled) - Donna Price-Machado (Cambridge, UK, 1998)
This book integrates English language instruction with the teaching of the competencies essential for succeeding on the job or in an academic setting. This theme-based and student-centered text from current newspapers get students reading, talking, and writing about such topics as building self-confidence, handling criticism, managing a successfull job interview, and making small talk with colleagues.
Keywords: english language - textbooks for foreign speakers